Hazard Analysis Critical Control Points (HACCP) – Getting Started, Preliminary Steps - Ronald H. Schmidt; Debby Newslow (EDIS)
FSHN07-01, a 4-page factsheet by Ronald H. Schmidt and Debby Newslow, reviews the preliminary steps that are necessary for putting a HACCP program into place and includes tips for making sure the process happens smoothly. Published by the UF Department of Food Science and Human Nutrition, June 2007.